Targeting of eugenol-loaded solid lipid nanoparticles to the epidermal layer of human skin. (August 2014) - Garg, Anuj; Singh, Sanjay
Aim: The purpose of this study was to formulate carbopol hydrogels containing eugenol-loaded solid lipid nanoparticles (EG–SLNs) for epidermal targeting to treat fungal infections in skin.Materials & methods: EG–SLNs were incorporated into carbopol hydrogels and the physiochemical characteristics of EG–SLN in hydrogels were investigated by dynamic light scattering, transmission electron microscopy and atomic force microscopy. Rheological behavior and mechanical properties of hydrogels were also studied before and after incorporation of EG–SLNs. The epidermal-targeting ability of EG–SLN-enriched hydrogels was evaluated by estimation of eugenol in the epidermis of human cadaver skin. An occlusion (hydration) study was also performed to elucidate the mechanism of epidermal targeting of EG–SLN-enriched hydrogels.Results: The particle size (d90) and morphology of EG–SLNs were not significantly changed after incorporation into the hydrogel. EG–SLN of stearic acid-enriched hydrogels follow the Carreau model that describes pseudoplastic flow. The hydrogel containing EG–SLN of stearic acid and of Compritol ® (Gattefose, Mumbai, India) showed significantly greater accumulation of eugenol in the epidermis (62.65 ± 4.35 and 52.86 ± 3.76 µg/cm 2, respectively) than that of eugenol–hydroxypropyl-β–cyclodextrin complex in hydrogel (9.77 ± 1.16 µg/cm 2 ) and almond oil solution of eugenol (3.45 ± 0.6 µg/cm 2 ). The occlusion study demonstrated greater hydration of human cadaver skin treated with EG–SLN-enriched hydrogel compared with that of hydrogel and intact skin.Conclusion: Hydrogels containing EG–SLNs could be a promising formulation for epidermal targeting to treat fungal infections in skin. Original submitted 26 March 2012; Revised submitted 29 January 2013